Seorang Perempuan Terinfeksi Tuberkulosis dengan Manifestasi Sindroma Distres Napas Akut (ARDS): [Acute Respiratory Distress Syndrome as a Manifestation of Tuberculosis in a Woman: A Case Report] - Putu Dyah Widyaningsih; Winariani Koesoemoprodjo (Jurnal Respirasi, 2016)
Tuberculosis remains a global issue throughout the world. Indonesia currently ranks 4th worldwide. Although rarely reported, TB could be one of the etiologies of Acute Respiratory Distress Syndrome. A 27-year-old woman was admitted with shortness of breath 12 days post partum with cough, loss of appetite and malaise. Chest examination revealed increased fremitus on both lungs and rhonchi on 2/3 lower part of the lung. There was edema on both of the leg. Radiologic finding suggested reticulogranuler pattern on both lungs. Laboratory showed granulocytosis, anemia and hypoalbumin with severe hypoxemia and PaO2/FIO2 ratio of 107. Transthoracic Echocardiography showed PCWP of 12,25 mmHg. Patient was diagnosed with moderate Acute Respiratory Distress Syndrome but there was no improvement after definitive antibiotic therapy. Based on clinical judgment, patients suspected of having tuberculosis and given anti tuberculosis drugs with a regimen of rifampicin, isoniazid, ethambutol, pyrazinamide, and streptomycin along with methylprednisolone and supportive therapy. Microscopic examination of acid-fast bacilli sputum shows positive result one day after the treatment started. Patient was showing significant improvement and declare cured after completed 6 month of therapy. Conclusions: Although the incidence is rare, tuberculosis can act as the primary cause of ARDS. Early diagnosis of tuberculosis is the key point of this case. Initial therapy along with good supportive therapy should be given to ARDS patient while the underlying cause is treated.